Outcomes of Rural-Urban Migration in Tanzania - Banyikwa, W. (Tanzania Journal for Population studies and Development, 2009)
This article discusses outcomes of rural-urban migration as part of a wider debate on urbanization and socio-economic development in mainland Tanzania. It presents empirical evidence from cities in the south-western, north-western and north-eastern parts of mainland Tanzania, and from a municipality in the eastern part of the country that links rural-urban migration to sanguine outcomes in selected elements of urban livelihoods. The results show that, while the earlier crop of migrants in the country comprised target workers, the current one is comprised of people who have more permanent interests in the towns. Also, where vertical mobility was a significant component of the drift to towns, rural-urban migration, urbanisation and socio-economic development in the studied towns were compatible. Migrants are a vital resource that should be harnessed for socio-economic development of the country.